Modeling Mama's Heart Movement on Decreasing Debris Index among Elementary School Students - Marsum; Santoso, Bedjo (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Health problems are suffered a lot around the world, one of which is dental caries. Based on the study's results, as many as 93% of children aged 5-6 years experienced dental caries, with an average experience of dental caries (dmf-t) of 8.3. World Health Organization (WHO) data shows that 90% of children have caries, and the ECC prevalence of children aged 5-6 years in Indonesia is 90.05%. This figure is still very far from expectations compared to the WHO target, which states that in 2020 the child's DMF-T value is one, and the Indonesian Ministry of Health targets to be caries-free by 2030. Objective: The study aimed to examine the effect of Modelling Mama’s Heart Movement to Decrease Debris Index in Elementary School Students. Method: Quasi-experiment with pre-posttest design, and the statistical test used is the Wilcoxon test. Results: The results are Wilcoxon's test with a p-value of 0.000, meaning that there is a significant change between the debris index scores before and after treatment in students. Recommendation Modelling Mama's Heart Movement can effectively decrease debris index and be an alternative problem-solving in school children's dental hygiene